Young Entrepreneurship for the Development of Sustainable Corporate Governance in Nepal - Sapkota, Arjun Prasad (Academia Journal of Humanities & Social Sciences, 2026)
This paper aims to investigate the influence of young entrepreneurship on the evolution of sustainable corporate governance in Pokhara Metropolitan City, Nepal. The study employed a mixed-methods approach and analyzed the data from 36 young entrepreneurs through a survey and semi-structured interviews with six people to evaluate the awareness, practices, and difficulties related to the modern corporate governance principles. The findings of the study show that young entrepreneurs in Pokhara Metropolitan City exhibit moderate levels of awareness of formal corporate governance principles (mean familiarity score: 3.47), with strong adherence to core operational practices. In particular, this study shows a predominant emphasis to specific area of tax compliance (mean: 4.58) and systematic financial record-keeping (mean: 4.42) and relatively less focus to the area of engagement with advanced methods, where regular stakeholder meetings (mean: 3.58) are presented. Interestingly, modernization occurs via digital tools such as significant barriers include administrative e-complications (mean: 3.75), lack of knowledge (mean: 3.25), and resource shortages (mean: 3.14). The qualitative data through interviews reveal a tension between traditional informal practices and professional models. The findings suggest a need for specific training, policy changes, and support. This study fills empirical gaps and offers implications for policymakers, educators, and business associations in creating accountable and innovative governance frameworks to enhance economic resilience and attract investors.